2012
DOI: 10.3846/16111699.2011.620155
|View full text |Cite
|
Sign up to set email alerts
|

Does TQM Support Innovation Performance in Malaysia's Manufacturing Industry?

Abstract: This empirical study examines the association of TQM practices (i.e. leadership, customer focus, strategic planning, people management, information analysis and process management) with the innovation performance as perceived by the managers in Malaysia. The research model is constructed on the basis of established theory and on well-known criteria such as Malcolm Baldrige National Quality Award. Six hypotheses are formulated and tested by multiple regression based on a sample of 206 managers working in the IS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 101 publications
(143 reference statements)
5
83
2
Order By: Relevance
“…Cemal et al [20] conducted a questionnaire survey with 261 middle and upper level managers of 104 manufacturing, information technology, and service companies of varying sizes in Turkey. Their conclusions from this study corresponded with the conclusions of Ooi et al [19] in Malaysia.…”
Section: Previous Studies On the Relationship Between Tqm Practices Asupporting
confidence: 92%
See 1 more Smart Citation
“…Cemal et al [20] conducted a questionnaire survey with 261 middle and upper level managers of 104 manufacturing, information technology, and service companies of varying sizes in Turkey. Their conclusions from this study corresponded with the conclusions of Ooi et al [19] in Malaysia.…”
Section: Previous Studies On the Relationship Between Tqm Practices Asupporting
confidence: 92%
“…Employees need to be reminded and pushed constantly to achieve the organisation's goals. The study of Ooi et al [19] , which was based on managers working in manufacturing organisations in Malaysia, confirmed that innovation performance is closely linked with several TQM practices such as people management, process management, customer focus, and strategic planning. Cemal et al [20] conducted a questionnaire survey with 261 middle and upper level managers of 104 manufacturing, information technology, and service companies of varying sizes in Turkey.…”
Section: Previous Studies On the Relationship Between Tqm Practices Amentioning
confidence: 92%
“…Smaller firms might find it difficult to maintain the levels of slack needed for considerable R&D investments and resource allocation decisions might become even more complex. Looking further into international firms, especially those in developing countries might be necessary given the essential role of innovation in attaining and sustaining competitive advantage in developing countries where industrial growth has become integral to economic development (Ooi et al 2012). Firms in developing countries in hypercompetitive global environments that seek long-term success are increasingly focusing on innovation and shifting away from cost reduction efforts.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting note from Ooi et al, (2012) that India has to make enormous effort to increase its innovation potential. On aggregation, India is the fourth largest consumer of resources and the largest ecological destructor among those countries surveyed (Selles, 2013).…”
Section: Discussionmentioning
confidence: 99%